2011
DOI: 10.1371/journal.ppat.1002453
|View full text |Cite
|
Sign up to set email alerts
|

Ce-Duox1/BLI-3 Generated Reactive Oxygen Species Trigger Protective SKN-1 Activity via p38 MAPK Signaling during Infection in C. elegans

Abstract: Infected animals will produce reactive oxygen species (ROS) and other inflammatory molecules that help fight pathogens, but can inadvertently damage host tissue. Therefore specific responses, which protect and repair against the collateral damage caused by the immune response, are critical for successfully surviving pathogen attack. We previously demonstrated that ROS are generated during infection in the model host Caenorhabditis elegans by the dual oxidase Ce-Duox1/BLI-3. Herein, an important connection betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
161
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(176 citation statements)
references
References 56 publications
15
161
0
Order By: Relevance
“…Hoeven et al . (2011) have shown that ROS released from Ce‐Duox1/BLI‐3 can activate SKN‐1 activity via p38 MAPK signaling, with NSY‐1 and SEK‐1 both able to regulate the p38 MAPK ortholog PMK‐1. In response to oxidative stress, PMK‐1 phosphorylates SKN‐1, which then translocates to the nuclei of intestinal cells and induces the transcription of phase 2 detoxification genes (Inoue et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Hoeven et al . (2011) have shown that ROS released from Ce‐Duox1/BLI‐3 can activate SKN‐1 activity via p38 MAPK signaling, with NSY‐1 and SEK‐1 both able to regulate the p38 MAPK ortholog PMK‐1. In response to oxidative stress, PMK‐1 phosphorylates SKN‐1, which then translocates to the nuclei of intestinal cells and induces the transcription of phase 2 detoxification genes (Inoue et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate colonization during coinfection of the intestine, an adaptation of a previously used methodology was employed (41). After the nematodes were infected as described above and allowed to incubate for 4 or 7 days, they were washed with 2 ml of sterile M9W and collected by centrifugation at 1,000 rpm four times.…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to RNAi, survival assays, and longevity assays were performed as previously described (Garsin et al , 2003Kim et al 2002;van der Hoeven et al 2011). Briefly, for E. faecalis survival assays, E. faecalis grown in brain heart infusion (BHI) medium for 5 hr was seeded (10 ml) onto BHI plates (gentamycin 50 mg/ml) and incubated at 37°for 24 hr, whereas for P. aeruginosa survival assays, P. aeruginosa was cultured in Luria broth (LB) overnight at 37°, seeded (10 ml) onto slow-killing plates, and incubated first for 24 hr at 37°and then for the duration of 516 G. R. Tiller and D. A. Garsin the experiment at 25°.…”
Section: Survival and Longevity Assaysmentioning
confidence: 99%